Choice of Media for Cultivation and Cryopreservation of Bone Marrow Stromal Cells - Lavrik, Aleksey A.; Trifonova, Anna V.; Gulevskiy, Aleksandr K. (Problems of Cryobiology and Cryomedicine, 2015)
N/A Probl Cryobiol Cryomed 2015; 25(1):81-85.